2010
DOI: 10.1177/1947601910369817
|View full text |Cite
|
Sign up to set email alerts
|

CDK Inhibitors Roscovitine and CR8 Trigger Mcl-1 Down-Regulation and Apoptotic Cell Death in Neuroblastoma Cells

Abstract: Neuroblastoma (NB), the most frequent extracranial solid tumor of children accounting for nearly 15% of all childhood cancer mortality, displays overexpression of antiapoptotic Bcl-2 and Mcl-1 in aggressive forms of the disease. The clinical phase 2 drug roscovitine (CYC202, seliciclib), a relatively selective inhibitor of cyclin-dependent kinases (CDKs), and CR8, a recently developed and more potent analog, induce concentration-dependent apoptotic cell death of NB cells (average IC 50 values: 24.2 µM and 0.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 80 publications
8
66
0
Order By: Relevance
“…Recent studies have shown a correlation between high expression of antiapoptotic factors Mcl-1 and Bcl-2 and resistance to therapy in neuroblastoma (6). Mcl-1 depletion via RNA interference induced apoptosis in neuroblastoma cell lines and sensitized them to cytotoxic chemotherapy, suggesting that Mcl-1, as well as Bcl-2, might be promising targets for neuroblastoma treatment (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown a correlation between high expression of antiapoptotic factors Mcl-1 and Bcl-2 and resistance to therapy in neuroblastoma (6). Mcl-1 depletion via RNA interference induced apoptosis in neuroblastoma cell lines and sensitized them to cytotoxic chemotherapy, suggesting that Mcl-1, as well as Bcl-2, might be promising targets for neuroblastoma treatment (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…PHA76749, a dual cdc7/CDK9 inhibitor, also induces a reduction in Mcl-1 transcript expression causing apoptosis in CLL cells stimulated with CD154/IL-4, indicating that CDK9 targeting may be sufficient to induce CLL cell apoptosis in the lymph node microenvironment (37). As shown previously, Mcl-1 expression may also be regulated at the posttranscriptional level, due to the abrogation of Mcl-1 protein expression (16,30,37). Mcl-1 proteasomal degradation, coupled with maintenance or upregulation of proapoptotic, Mcl-1-binding partner Noxa upon treatment of cells with CR8, roscovitine, or PHA767491 can drive cells toward apoptosis (30,37).…”
Section: Discussionmentioning
confidence: 82%
“…Ã , P < 0.05; ÃÃ , P < 0.005; ÃÃÃ , P < 0.001. CR8 exhibited only a modest improvement as a CDK inhibitor compared with roscovitine, despite an enhanced ability to induce CLL apoptosis (19,30), whereas CR8 was less potent than flavopiridol at inhibiting CDK2 and CDK9 but induced CLL cell death in the same nanomolar range. These findings may reflect differences in the kinome each clincancerres.aacrjournals.org Downloaded from drug interacts with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 25% of biliary tract tumors harbor CDKN2A mutations (as shown in the COSMIC database in November 2012).Tumors with loss of the CDKN2A/ CDKN2B locus may be sensitive to Cdk4/6 inhibitors, and clinical trials of these agents are currently under way for a variety of solid tumors. Of additional interest is the observation that, given the relatively frequent 21% rate of MCL1 focal gene amplification in the ICC cohort, CDK inhibitors may function by reducing MCL1 protein levels as their main mechanism of action [39].…”
Section: Discussionmentioning
confidence: 99%